Decision tree analysis to identify harmful contingencies and estimate blackout indices for predicting system vulnerability - Aliyan, Ehsan; Aghamohammadi, Mohammadreza; Kia, Mohsen; Heidari, Alireza; Shafie-khah, Miadreza; Catalão, João P.S. (Elsevier, 2020)
Cascading failure is the main mechanism for progressing large blackouts in power systems. Following an initial event, it is challenging to predict whether there is a potential for starting cascading failure. In fact, the potential of an event for starting a cascading failure depends on many factors such as network structure, system operating point and nature of the event. In this paper, based on the application of decision tree, a new approach is proposed for identifying harmful line outages with the potential of starting and propagating cascading failures. For this purpose, associated with each trajectory of the cascading failure, a blackout index is defined that determines the potential of the initial event for triggering cascading failures towards power system blackout. In order to estimate the blackout indices associated with a line outage, a three stages harmful estimator decision tree (HEDT) is proposed. The proposed HEDT works based on the online operating data provided by a wide area monitoring system (WAMS). The New England 39-bus test system is utilized to show the worthiness of the proposed algorithm.
Keywords: blackout; cascading failure; decision tree; harmful line outage; electrical power networks; transmission of electricity; electric power failures; systems; modelling (creation related to information); reliability (general); power lines; electric power; effects (results); fi=Sähkötekniikka|en=Electrical Engineering|